Empreendedorismo educacional e criação de conteúdo educomunicativo: a criação do site “educar bilíngue” para incentivar o bilinguismo na primeira infância - Reis, Ederlei Rodrigo dos (2022)
The project educational entrepreneurship and creation of educommunicative content: the creation of the website "Educar Bilíngue" to encourage bilingualism in early childhood, aims to promote the practice of bilingualism in children of the portuguese and english languages through playful content for parents and their children at an early age. The website is used to share content in a ludic narrative, as an educommunicative product with practical applications in everyday life. The proposal is born digital and using social midias to generate value for the brand. In addition, the business already has a social meaning as an integral part of this creation, since the "Educar Bilíngue" will have content available for free for all parents who want to devote time to the development of their children, but who do not have the financial resources to invest in paid content. To build this work, na empirical research was conducted with directed propositions. So, the proposal identified in the research, theoretically based on precepts in the area of Technology of Information and Communication, Educational Entrepreneurship, Bilingual Education, is to show how a website can foster and leverage children's bilingual education, through the support of parents who share content and experiences in the education of their kids in a second language, creating a valuable brand for the modern consumer. As strong points we highlight the possibility of partnerships with thematic content creators, possibility of new business aggregates, relationship building and not persuasion, 100% digital material production, and interfaces with other areas.